Analysis of business development strategies using the business model canvas and SWOT: A case study of Jubela Agrikarsa - Hibatullah, Raihan; Bangsawan, Satria (Lighthouse Publishing, 2025)
This study explores the business development strategies of CV. Jubela Agrikarsa, a Small and Medium Enterprise (SME) in Bandar Lampung specializing in poultry products. By employing the Business Model Canvas (BMC) and SWOT analysis, the research identifies critical internal and external factors influencing the company’s growth and strategic positioning. The findings highlight Jubela Agrikarsa's strengths, such as high product quality and strategic location, and weaknesses, including limited business experience and insufficient promotion. The analysis also uncovers opportunities in market expansion and threats from rising competition. The study provides actionable recommendations to address these challenges, such as enhancing operational efficiency, improving branding efforts, and leveraging digital marketing platforms. This comprehensive approach not only aids Jubela Agrikarsa in refining its business strategies but also demonstrates the efficacy of BMC and SWOT as strategic tools for SMEs in competitive markets.